THE ROLE OF ADOLESCENT POSYANDU IN IMPROVING ADOLESCENTS' KNOWLEDGE AND CONCERN TOWARDS HEALTH IN RAHAYU VILLAGE, SOKO DISTRICT, TUBAN REGENCY - Amarullah; Nurul Jariyatin; Sony Aditya Kusuma; Zuhryansah (Jurnal Humanis ( Jurnal Pengabdian Masyarakat ISTeK ICsada Bojonegoro), 2025)
Adolescent Posyandu is a program that aims to improve adolescent knowledge and awareness of health through counseling and providing relevant health services. This study aims to examine the role of Adolescent Posyandu in Rahayu Village, Soko District, Tuban Regency, in improving adolescent knowledge about health and encouraging their awareness of health problems. This program is the result of collaboration between Pertamina EP and ISTek ICsada Bojonegoro. This study used a survey method with a qualitative approach. The results showed that the Adolescent Posyandu in Rahayu Village succeeded in increasing adolescent knowledge and awareness of healthy lifestyles, reproductive health, and the importance of exercise and balanced nutrition. Participants who participated in adolescent posyandu activities ranged from 20-25. However, improvements are still needed in terms of active participation of adolescents and utilization of health services available at the Posyandu.